Implementation of a Smart Home System Using IoT with Google Nest Integration for Lighting and Security Control - Herlian, Erwin; Irnawan, Dody; Farania, Azrina; Almukarimy, Irshad Haqqi (Sinektika: Jurnal Arsitektur, 2025)
This research explores the implementation of a smart home system using the Internet of Things (IoT) with Google Nest as a voice-command interface to control lighting and CCTV in residential environments. The system integrates smart touchscreen light switches and IP-based surveillance cameras within the Google Home ecosystem. Through design, installation, and user testing, the system was evaluated for functionality, convenience, and user satisfaction. The study found that voice control enhanced accessibility, while touchscreen switches offered practical manual control when needed. Real-time CCTV monitoring via IP cameras provided added home security. However, challenges such as internet dependency and post-blackout functionality of smart devices were identified. Overall, the research demonstrates the feasibility and benefits of integrating IoT in modern homes and presents a user-friendly model that could inform future smart residential designs. The findings were also validated through practical implementation, as documented in a video published by Herlian Architecture Studio.